Deep moist atmospheric convection in a subkilometer global simulation. Issue 18 (20th September 2013) - Miyamoto, Yoshiaki; Kajikawa, Yoshiyuki; Yoshida, Ryuji; Yamaura, Tsuyoshi; Yashiro, Hisashi; Tomita, Hirofumi
<x xml:space="preserve">Abstract</x> [1] Deep moist atmospheric convection is a key element of the weather and climate system for transporting mass, momentum, and thermal energy. It has been challenging to simulate convection realistically in global atmospheric models because of the large gap in spatial scales between convection (100 km) and global motions (104 km). We conducted the first ever subkilometer global simulation and described the features of convection. Through a series of grid‐refinement resolution testing, we found that an essential change for convection statistics occurred around 2 km grid spacing. The convection structure, number of convective cells, and distance to the nearest convective cell dramatically changed at this resolution. The convection core was resolved using multiple grids in simulations with grid spacings less than 2.0 km.